Microphase separation induced in the melt of Pluronic copolymers by blending with a hydrogen bonding urea–urethane end-capped supramolecular polymer1. Issue 29 (7th August 2015) - Hermida-Merino, Daniel; Newby, Gemma E.; Hamley, Ian W.; Hayes, Wayne; Slark, Andrew
<x xml:space="preserve">Abstract</x> Melt blending of a supramolecular polymer with a pluronic block copolymer leads to microphase separation.